Analisis Peran Pendistribusian Dana Zakat Produktif Dalam Meningkatkan Kesejahteraan Mustahik Pada Baznas Kabupaten Kampar - Zakir, Muhammad; Rahmawati, Rahmawati; Khairi, Rifqil; Putri, Berliana; Amalia, Nala (EL-EMIR Institute, 2025)
Distribution of productive zakat is one of the efforts made by BAZNAS Kampar Regency to improve the welfare of mustahik. The focus of this study is to analyze the role of zakat in improving the welfare of mustahik. This study uses a qualitative approach with a descriptive method. The data sources used consist of primary and secondary data, with data collection techniques through interviews, documentation, and literature reviews. In data analysis, data reduction techniques, data presentation, and drawing conclusions are used. The results of the study indicate that although productive zakat provides a positive role in empowerment and opening up economic opportunities, a further role from BAZNAS in mentoring and supervision is needed to ensure that zakat funds can be utilized optimally, leading to an increase in economic independence and more significant welfare.